2002
DOI: 10.1046/j.0022-202x.2001.01666.x
|View full text |Cite
|
Sign up to set email alerts
|

Type XVI Collagen is Expressed in Factor XIIIa+ Monocyte-Derived Dermal Dendrocytes and Constitutes a Potential Substrate for Factor XIIIa

Abstract: We have previously reported that connective tissue cells in the superficial dermis preferentially express alpha1(XVI) collagen rather than those in the lower dermis. Double immunofluorescence labeling using the antibodies for alpha1(XVI) collagen and factor XIIIa (plasma transglutaminase), which is a marker of dermal dendrocytes, demonstrated that both antibodies reacted with the same cells in the superficial dermis of normal skin as well as the lesional skins of dermal dendrocyte-related disorders, dermatofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
(68 reference statements)
3
27
0
Order By: Relevance
“…A significant elevation of FXIII-A mRNA and protein level was observed during monocyte/macrophage differentiation in cell culture [30,31] and TG-2 also became up-regulated [32][33][34]. Induction of in vitro differentiation of monocytes into antigen presenting dendritic cells resulted in highly elevated FXIII-A expression [35][36][37].…”
Section: Expression Of Fxiii In Monocytes/macrophages and Its Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant elevation of FXIII-A mRNA and protein level was observed during monocyte/macrophage differentiation in cell culture [30,31] and TG-2 also became up-regulated [32][33][34]. Induction of in vitro differentiation of monocytes into antigen presenting dendritic cells resulted in highly elevated FXIII-A expression [35][36][37].…”
Section: Expression Of Fxiii In Monocytes/macrophages and Its Changesmentioning
confidence: 99%
“…However, a few studies indicated that in cultured cells it could be translocated to the surface [26,30,39]. The appearance of FXIII-A in the culture medium suggested its secretion by dendritic cells [37]. However, dying or dead cells may be the source of cell surface associated or soluble phase FXIII.…”
Section: Intracellular Localization Of Fxiii In Monocytes/macrophagesmentioning
confidence: 99%
“…It is synthezised by dermal fibroblasts, smooth muscle cells (Grässel et al, 1996), dermal dendrocytes and dendritic cells in the skin (Akagi et al, 2002), articular and costal chondrocytes (Kassner et al, 2003), endometrial stromal cells (Tierney et al, 2003), basal dermal and oral keratinocytes (Grässel et al, 1999), bone marrow derived mesenchymal stem cells (Grässel et al, 2009), neurons from the dorsal root ganglion (Hubert et al, 2007), glioblastoma/astrocytoma cells (Senner et al, 2008) and intestinal myofibroblasts (Ratzinger et al, 2010). Collagen type XVI is further expressed in the limbal stem/progenitor niche which comprises clusters of cells in the basal epithelium.…”
Section: Expressionmentioning
confidence: 99%
“…Change in the FXIII-A-positive dermal dendrocytes is characterized by intense cytoskeletal reorganization resulting in many cellular functions and improvement of tensegrity. The intracellular activity of FXIII-A may be responsible for proliferation, differentiation, migration, survival and excessive inflammatory cytokine secretion of dermal dendrocytes [5,6,8,9,12,15].…”
Section: Fxiii-a In Inflammatory Skin Lesionsmentioning
confidence: 99%
“…FXIII-A, as a potential active subunit is also present in the cytoplasm of platelets, monocytes, macrophages, dendritic cells, chondrocytes, osteoblasts, and osteocytes. It can be detected from the early stage of monoblasts in the bone marrow via blood monocytes to the connective tissue macrophages [4][5][6][7][8][9][10][11]. FXIII-A is considered as a positive marker protein of the cell line in which it acts as an intracellular transglutaminase with roles in various intracytoplasmatic and intranuclear processes.…”
Section: +mentioning
confidence: 99%